2017
DOI: 10.1515/sbe-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

Urban Farm-Nonfarm Diversification, Household Income and Food Expenditure in Ghana

Abstract: Abstract:This paper investigates the impact of farm-nonfarm diversification (FND) on household income and food expenditure in urban Ghana using propensity score matching (PSM) technique to account for potential selection bias. We find diversified households to be statistically different from undiversified households in terms of household characteristics. Age, gender, educational attainment of the household head, household size, ownership of livestock and agricultural land, and receipt of miscellaneous and rent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(26 reference statements)
2
2
0
Order By: Relevance
“…The probable reason is that age of the household helps to participate in additional income source through experience. This result is consistent with a study by Ampaw, Nketiah-Amponsah, and Senadza (2017) in Ghana, who found a positive relationship between the age of farmers and the probability of their participation in non-farm and off-farm activities.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The probable reason is that age of the household helps to participate in additional income source through experience. This result is consistent with a study by Ampaw, Nketiah-Amponsah, and Senadza (2017) in Ghana, who found a positive relationship between the age of farmers and the probability of their participation in non-farm and off-farm activities.…”
Section: Resultssupporting
confidence: 93%
“…For one unit increase in the value of livestock, the probability of participation in both agriculture and non-agriculture sources of income generation would increase by 12.2%. This result is in line with the findings by Ampaw, Nketiah-Amponsah, and Senadza (2017) and Yizengaw (2014) who found a positive relationship between the number of livestock and the probability of participation in non-farm and off-farm activities.…”
Section: Resultssupporting
confidence: 92%
“…We excluded studies on nonfarm diversification although we are aware that they can be critical strategies to increasing food security (e.g. Ampaw et al, 2017;Barrett et al, 2001) but we consider studies on agricultural activities that increase farmer's income as a component of food access. We also exclude studies that discuss benefits of specific crops without also clearly stating that agricultural diversity increases overall, for example high-value or wild crops (Mavengahama et al, 2013) or crops perceived as being underutilized or neglected (Kahane et al, 2015;Mabhaudhi et al, 2017Mabhaudhi et al, , 2016.…”
Section: Search Criteria and Methodsmentioning
confidence: 99%
“…Many researchers research farmers' household income in various countries, such as urban agricultural households' impact on food security status (Fei et al, 2020). Food insecurity (Mcdougall et al, 2020) in Ibadan Metropolis, agricultural and non-agricultural diversification on household income (Kansiime et al, 2021), the existence of urban agricultural households in Maseru can support food security (Galli et al, 2020), the contribution of integrated urban agriculture to household income in Kinondoni Municipality (Yusuf et al, 2015), as well as determinants of household income between urban and rural areas with different characteristics in terms of poverty in India (Ampaw et al, 2017). However, there has not been a study that investigates the household income of urban farmers by utilizing a qualitative independent variable regression, which analyzes the relationship between different agricultural production areas and its impact on household income.…”
Section: Introductionmentioning
confidence: 99%